2019
DOI: 10.25299/jeee.2019.vol8(1).2909
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Steam Flooding Injection Patterns and Steam Quality to Recovery Factor

Abstract: The main principle of steam flooding is to reduce the oil viscosity using hot steam that is injected into the reservoir. In the field implementation there are several injection patterns that can be applied for steam flooding. This research aims to determine the effect of several injection patterns and steam quality on oil recovery factor. Therefore, it can be known the injection pattern and steam quality are right to obtain the best recovery factor. Analysis was carried out on injection patterns including five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Dixon and Nguyen [18] studied forecasting algorithms, models of hot water and steam production systems, and came to the conclusion that there are opportunities to optimize the design of boilers and heat supply systems. Kusumastuti et al [19] considered the processes of vaporization and injection of condensate into steam to change its parameters and came to the conclusion that the systems of vaporization and steam supply require improvement.…”
Section: Review Of Work On the Research Topicmentioning
confidence: 99%
See 1 more Smart Citation
“…Dixon and Nguyen [18] studied forecasting algorithms, models of hot water and steam production systems, and came to the conclusion that there are opportunities to optimize the design of boilers and heat supply systems. Kusumastuti et al [19] considered the processes of vaporization and injection of condensate into steam to change its parameters and came to the conclusion that the systems of vaporization and steam supply require improvement.…”
Section: Review Of Work On the Research Topicmentioning
confidence: 99%
“…where p-pressure of the transported two-phase medium. The thermal equilibrium equation for the liquid phase is expressed in thermal equation (19).…”
Section: Parametermentioning
confidence: 99%
“…However, the full benefit of it is also depending on the injection pattern used in this method. Kusumastuti et al (2019) found that inverted seven-spot will give the full benefit of recovery. Thermal injection could replace resources to reserves that thermal injection plays a crucial role in the development of heavy oil for the future projects, which one of them is electrical heating.…”
Section: Thermal Injectionmentioning
confidence: 99%
“…However, the technique presents some major challenges, such as steam over-ride, heat loss, and low thermal conductivities of the rocks. The steam quality (X) influences the displacement efficiency and the viscosity reduction, and other mechanisms that help determine optimum flooding conditions [10][11][12][13]. It is well known that the steam quality and temperature affect the oil recovery from the steam flooding process, reducing the oil production by more than 50% when X = 0.5 [14].…”
Section: Introductionmentioning
confidence: 99%